Colonoscopy and the psyche – pain and discomfort associations with affect and cognitive functions - Zaczek, Adam; Pietrasińska-Wojna, Anna; Szczegielniak, Anna; Girczys-Połedniok, Katarzyna; Dębski, Paweł; Pudlo, Robert (Current Problems of Psychiatry, 2024)
Introduction: Colonoscopy is an important diagnostic and therapeutic procedure, however it causes considerable discomfort in patients. Their psychological functioning is sometimes not sufficiently taken into account by the medical staff, preoccupied with somatic conditions. The aim of this study was to reveal affective and cognitive aspects of how patients undergoing colonoscopy function in order to better understand periprocedural discomfort and pain and suggest interventions to reduce them. Material and methods: A total number of 101 patients, undergoing colonoscopy during their stay at the internal ward, were asked to participate in this prospective, observational study. Three measurements were made: the day before the examination, on the colonoscopy day (after bowel cleansing, before the procedure) and the following day. The State-Trait Anxiety Inventory, Beck Depression Inventory II, Montreal Cognitive Assessment, short version of The Illness Perceptions Questionnaire , as well as analog scales (measuring pain, sadness, anxiety, irritability, general discomfort and distress) were used. Ultimately, 50 people completed the study. Results: It has been shown that pain and discomfort on the colonoscopy day correlate positively with all measured aspects of negative affect. On the colonoscopy day 18% of the subjects revealed depressive symptoms matching a depressive episode, while 56.6% of the subjects displayed a high level of state anxiety. The worse the patient’s understanding of the disease, the more periprocedural pain he/she experiences. Their cognitive functioning is worse on the colonoscopy day. Conclusions: The results suggest that it is advisable to educate patients early enough (not on the day of the procedure) about their ailments and planned colonoscopy.